In Utero Repair of Spina Bifida - Moldenhauer, Julie S. (American Journal of Perinatology, 2014)
Open spina bifida or myelomeningocele (MMC) is the most common congenital malformation of the central nervous system compatible with long-term survival and is associated with significant lifelong disabilities. Postnatal care of MMC involves covering the exposed spinal cord, infection prevention, and ventricular shunting for hydrocephalus. The aim of postnatal MMC surgery is not to reverse or prevent the neurologic injury seen in MMC, but to palliate. The neurologic defects result from primary incomplete neurulation and secondary chronic in utero damage to the exposed neural elements through mechanical and chemical trauma—the two-hit hypothesis. With the ability to accurately diagnose spina bifida prenatally and the concept of the two-hit hypothesis, in utero repair to decrease exposure and alter the antenatal course of neurologic destruction was conceived. Through animal models and human pilot studies, the feasibility of fetal spina bifida repair was demonstrated. Subsequently, the prospective randomized multicenter Management of Myelomeningocele Study (MOMS trial) revealed a decreased need for shunting, reversal of hindbrain herniation, and preservation of neurologic function, making in utero repair an accepted care alternative for select women carrying a fetus with spina bifida. This article will highlight the background and rationale for in utero repair, and the progression to becoming an alternative standard of care. The future directions of fetal spina bifida repair will also be addressed.
Keywords: fetal surgery; myelomeningocele; prenatal diagnosis; spina bifida